Aircraft Wake Vortices Affecting Airport Wind Measurements - Krummen, Jan; Noelke, Lena; Monstein, Raphael (Journal of Open Aviation Science, 2023)
The influence of wake vortices on other aircraft has been extensively studied and is well understood. However, to date, it has not been investigated how wake vortices can affect wind velocity measurements at airports. This study investigates this previously overlooked issue, focusing on departures from runway 34 at Zurich Airport. These departures are suspected to affect a wind sensor situated at the runway's end. Through a combination of visual identification and application of a wake vortex model, instances where wakes affected the said anemometer were identified for a fifteen-month period. Analysis of the resulting data shows that approximately 5% of all departures generated such occurrences. In addition, specific wind conditions and aircraft types were identified as being necessary for such events to occur. The observed cases of wake hits have a significant effect on the wind measurements, altering even averaged values used by air traffic control for clearance by several knots and up to 50 degrees. That, in turn, can result in cases where aircraft performance does not allow take-off based on altered wind readings, even though the actual wind conditions would not prevent the departure. Such cases have the potential to cause significant disruption to flight operations. Even though this paper focuses on this phenomenon at Zurich Airport, similar issues are likely to occur at other airports as well.